2015
DOI: 10.5812/jjm.22582
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Genetic Characterization of Metallo-β-Lactamase IMP-1 and VIM-2 in Pseudomonas aeruginosa Strains From Different Hospitals in Kermanshah, Iran

Abstract: Background:Pseudomonas aeruginosais a frequent nosocomial pathogen that causes severe diseases in many settings. Carbapenems, including meropenem and imipenem, are effective antibiotics against this organism. However, the use of carbapenems has been hampered by the emergence of strains resistant to carbapenemsvia different mechanisms such as the production of metallo-β-lactamases (MBLs), which hydrolyze all carbapenems. Several kinds of MBLs have been reported, among them VIM and IMP types being the most clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
2
9
1
Order By: Relevance
“…The imipenem disk diffusion screening divided 50 study isolates into two groups: 15 isolates (30%) of imipenem resistant and 35 isolates (70%) of imipenem sensitive P. aeruginosa. Similar results have been described by different authors [10,17,8,18,16] While, lower results were reported by [19] and higher results were published by. [20] So, it was noticed that the prevalence of IPM resistance varies greatly between and within countries and even between hospitals within a community and this could be attributed to the differences in antimicrobial usage and infection control practice in different localities.…”
Section: Discussionsupporting
confidence: 91%
“…The imipenem disk diffusion screening divided 50 study isolates into two groups: 15 isolates (30%) of imipenem resistant and 35 isolates (70%) of imipenem sensitive P. aeruginosa. Similar results have been described by different authors [10,17,8,18,16] While, lower results were reported by [19] and higher results were published by. [20] So, it was noticed that the prevalence of IPM resistance varies greatly between and within countries and even between hospitals within a community and this could be attributed to the differences in antimicrobial usage and infection control practice in different localities.…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, from 278 imipenem-resistant P. aeruginosa and 187 imipenem-resistant A. baumannii isolates, 178 and 85 isolates were MBL-producers, respectively. Large outbreaks by MBL-producing P. aeruginosa strains were described in hospitals in Greece, Italy and Korea (27 was not detected in the isolates. Also, in a similar study in India, 47% of A. baumannii isolates carried bla VIM and 0.9% of them harbored bla IMP (29).…”
Section: Discussionmentioning
confidence: 86%
“…The bla IMP and bla VIM -producing P. aeruginosa strains are reported worldwide (27). The rapid diagnosis of MBL isolates is helpful to select suitable options for antimicrobial therapy and prevent the spread of MBL strains.…”
Section: Discussionmentioning
confidence: 99%
“…As for non baumannii species, only one study reported the detection of OXA-23 and SPM producing Acinetobacter nosocomialis in patients with blood infections (Pourabbas et al, 2016). In P. aeruginosa , MBLs were the most common carbapenemases including: IMP (IMP-1 and IMP-55) and VIM variants (VIM-1, VIM-2) (Abiri et al, 2015; Lari et al, 2015; Mirbagheri et al, 2015; Moosavian and Rahimzadeh, 2015; Azizi et al, 2016; Saffari et al, 2016; Kazeminezhad et al, 2017; Dogonchi et al, 2018; Pournajaf et al, 2018; Rostami et al, 2018). Only two studies reported the detection of OXA-23 and SPM-1 in Iranian clinical isolates of P. aeruginosa (Ostad Asadolah-Malayeri et al, 2016; Azimi et al, 2018).…”
Section: Distribution Of Multi-drug Resistant Organisms In Humansmentioning
confidence: 99%